Enhancing the Implementation of the National Waste Management Strategy in Greater Sekhukhune - Masemola, Seporo Sam Addison (My University, 2011)
This research was conducted with the aim of finding out why medical waste that is often found illegally disposed of and who is responsible for it. Such waste poses a danger to people, animals and the environment. The researcher has visited health care waste generators (and the landfill site) in the area under review and conducted a number of interviews with different stakeholders. The findings indicated that hospitals in the area were found to be the main sources of illegal dumping. The research recommends a continuous intensive health education process for all personnel working with medical waste management. Private commercial providers should also be organised into jointly contracting a service provider who will collect their medical waste and dispose of it appropriately. The researcher highly recommends that all medical waste generators in the area be registered and a collection method be jointly found to rid the area of the dangers of incorrectly handling and disposing of medical waste. Public-Private Partnerships can also be explored to help sustain the medical waste management strategy.
MM thesis - P&DM
Keywords: Waste management; Medical waste; Public private partnerships